Affinity Study and Rock Types in the Beruang Kanan Area, Central Kalimantan - Anjarwati, Retno; Sutarto, Sutarto; Yudiantoro, Dwi Fitri; Idrus, Arifudin (Riviera Publishing, 2025)
The mineralizing bearing rocks on the Right Bear prospect are andesite. Geochemical data of rocks indicate that they are classified as intermediate igneous rocks rich in silica. The composition of andesite silica is approximately 60% with a total alkali (Na+K) of about 3.6%. Based on this data, it is known that the dacite affinity is calc-alkaline. The volcanic rocks of the Right Bear prospect are primarily andesite. This study aims to determine the affinity of magma and geochemical characteristics of volcanic rocks in the Beruang Kanan area, Central Kalimantan, as the basis for the interpretation of tectonic settings and mineralization potential. Geochemical analysis was carried out using the X-Ray Fluorescence (XRF) method for the main oxide element and Inductively Coupled Plasma Mass Spectrometry (ICP-MS) for trace elements. Samples that have an LOI value of less than about 2% by weight are assumed to be unaltered or fresh rocks and these rocks are generally characterized by the presence of relative euhedral phenocrites and mineral grains and the absence of secondary hydrothermal minerals. The results of the comparison of Co and Th (Hastie, et al., 2007) on samples of fresh/slightly altered rocks and completely altered rocks are included in the affinity of magma of the alkaline limestone type. The results of the comparison of Zr/Y and Th/Yb (Ross & Bedard, 2009) show that samples of fresh rocks and altered rocks are included in the affinity of magma of the alkaline calcage series. Based on the results of the plotting of some of the above methods, it can be concluded that the magma affinity of the Beruang Kanan area belongs to the type of alkaline limestone which can be interpreted as being related to the within plate (in the plate) in the form of a continental expansion zone. This finding has important significance for the exploration of Cu-Au epithermal-porphyry mineralization in the Central Kalimantan region, given that rocks with calc-alkaline affinity in the within plate setting are often associated with economical mineralization systems.